Antispasmodic activity of Warionia saharae Benthem ex Benth. & Coss. on the rabbit and rat jejunums - Ouafa Amrani; Mohamed Marghich; Hanane Makrane; Chakib Alem; Mohammed Aziz (GarVal Editorial Ltda., 2021)
Context: Warionia saharae Benthem ex Benth. & Coss has been widely used for gastrointestinal problems in Morocco and Algeria. Aims: To explore the possible mechanism for its use to such ailments in order to rationalize some of these folkloric uses. We investigated the aqueous extract of this plant (AqWs) for antispasmodic activity on isolated rat and rabbit jejunums. Methods: To investigate the contractile activity of isolated jejunum preparations of rat and rabbit we had used in vitro techniques. Jejunums were suspended in tissue baths filled with KHB culture medium (37°C) and connected to force transducers. AqWs (0.1-3 mg/mL) was used with or without carbachol (10-6 M), KCl (25 mM), yohimbine (10-5 M), prazosin (10-5 M), propranolol (10-5 M), hexamethonium (10-4 M), atropine (10-6 M), methylene blue (10-5 M), L-NAME (10-4 M) and nifedipine (10-6 M). Results: AqWs at 0.1-3 mg/mL produced a relaxation on basal rabbit contractions with an IC50 = 1.55 ± 0.06 mg/mL. This effect was reversible and was not affected by pretreatment with the inhibitors of α and β adrenergic receptors yohimbine, prazosin and propranolol. The extract had an antispasmodic activity with an IC50 = 1.25 ± 0.02 mg/mL on rat jejunum precontracted with KCl rich medium (25 mM). This result suggests that the extract had a Ca2+ antagonist effect. This was fortified when pretreatment of the intestine with the extract induced a rightward shift in the Ca2+ concentration-response curves. AqWs exhibited also antispasmodic effect on carbachol (10-6 M)-induced contractions of rat jejunums with an IC50 = 1.53 ± 0.04 mg/mL. The extract at 3 mg/mL on rat jejunums pre-incubated with hexamethonium (10-4 M), atropine (10-6 M), and methylene blue (10-5 M), then contracted by KCl, decreased the maximum contraction but not totally like KCL alone without these inhibitors. For the jejunum pre-incubated with L-NAME (10-4 M), the spasmolytic effect of AqWs was comparable with KCL. Conclusions: These results suggest that the myorelaxant and antispasmodic effects are mediated possibly via Ca2+ antagonist, anticholinergic, and guanylate cyclase mechanisms but not by adrenergic and nitric oxide pathway.